Echocardiographic Study in Preterm Infant with Hemodynamic Significant Patent Ductus Arteriosus - Sunny Mariana Samosir; Martono Tri Utomo; Mahrus A. Rahman; Risa Etika; Dina Angelika; Kartika Darma Handayani; Agus Harianto (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Potential complications of hemodynamic significant patent ductus arteriosus (hsPDA) after birth include heart failure, need for respiratory support, renal disfunction, intraventricular hemorrhage, as well as long term altered growth and development. Nevertheless, clinical signs of patent ductus arteriosus (PDA) are not sensitive and specific enough. Therefore, echocardiography still remains the preferred method to evaluate the ductal patency in preterm infant. The present study aimed to evaluate the echocardiography characteristic in preterm infant with hsPDA.Methods: A cross-sectional study was conducted on preterm infants aged 3-7 days with 24-336/7 weeks of gestation. Data taken were demographic, clinical and echocardiography. Diagnosis of hsPDA was carried out by echocardiography; defined as >1.5mm diameter of ductus and >1.4 left pulmonal artery and aorta (La/Ao) ratio. The statistical analysis was undertaken using SPSS 21.0.Results: There were 11 out of 52 preterm infants diagnosed hsPDA. Mean birth weight was 1213±293 gram; Mean gestational age was 30.72±2.01 weeks. In hsPDA group, mean ductus diameter was 2.84±0.93 mm, mean La/Ao ratio was 1.56±0.26, and mean ejection fraction (EF) was 71.55±5.72%.Conclusion: Echocardiographic evaluation is important for addressing hsPDA in preterm infants.